Icings in the Selenge River basin as an indicator of climate change - Chernykh, Vladimir; Ayurzhanaev, Alexander; Shikhov, Andrey; Sodnomov, Bator; Zharnikova, Margarita; Khurelbaatar, Temuujin; Tsogoo, Bilguun; Enkhjargal, Undrakhbayar; Gagarin, Leonid; Gurzhapov, Bair; Badmaeva, Ariuna; Pyankov, Sergey; et al. (Mongolian Journal of Geography and Geoecology, 2025)
The Selenga River basin, with approximately two-thirds of its area located in Mongolia and the remaining third in Russia, hosts over 29,000 icings of diverse genetic types that form annually. In this study we analyzed the interannual variability of icings in the Selenga River basin. Using multi-temporal Landsat imagery, data from meteorological stations, hydrometric stations and expedition observations, the main trends in the change of icings formation intensity were established. Over the period from 1990 to 2024, a 3.5% decrease in the area of giant icings in the Mongolian part of the basin over 10 years was revealed. In the Russian part of the catchment basin, besides the reduction in the total area of icings by 6,7% over 10 years, an increase in the number of medium, small and very small ones is observed against the background of a decrease in the number of very large icings. The established trend is related to climate change. A significant increase in air temperature in April (on average in the basin by 0.75˚ over 10 years) may be one of the reasons for the overall reduction in the area of icings. As a result of the observed warming, the thickness of seasonal freezing of rocks decreases, which leads to an increase in the transition of icing-forming groundwater outside the icing fields. Also, melting of permafrost is recorded. Thus, icings are a kind of indicator of changes in permafrost-hydrogeological conditions under the influence of global climatic processes.